Vacancies in Metal−Organic Frameworks: Formation, Arrangement, and Functions. Issue 5 (12th May 2022) - Pang, Qingqing; Yang, Lingyi; Li, Qiaowei
Abstract : Vacancies in Metal–Organic Frameworks Vacancies such as missing organic linkers or inorganic clusters in metal–organic frameworks (MOFs) have been demonstrated to have a great impact on the materials properties. In article number 2100203, Qiaowei Li and co‐workers summarize the recent progress in the formation, arrangement, and functions of structural vacancies in MOFs. (Image: Yi Liu)